High Performance Computing Systems and Applications 23rd International Symposium, HPCS 2009, Kingston, ON, Canada, June 14-17, 2009, Revised Selected Papers - Mewhort, Douglas J. K.; Cann, Natalie M.; Slater, Gary W.; Naughton, Thomas J. (Lecture Notes in Computer Science,, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the 23rd International Symposium on High Performance Computing Systems and Applications, HPCS 2009, held in Kingston, Canada, in June 2009. The 29 revised full papers presented - fully revised to incorporate reviewers' comments and discussions at the symposium - were carefully selected for inclusion in the book. The papers are organized in topical sections on turbulence, materials and life sciences, bringing HPC to industry, computing science, mathematics, and statistics, as well as HPC systems and methods.